The Role Of The School Principal As A Learning Leader In Strengthening The Professionalism Of Batik Surakarta Junior High School - Sholihah, Isnaini Maratus (Universitas PGRI Semarang, 2024)
This article Â examines the role of the school principal as a learning leader in strengthening teacher professionalism at SMP Batik Surakarta. Teacher professionalism plays a crucial role in improving the quality of education in schools. Therefore, the school principal has a significant responsibility to motivate, inspire, and lead teachers in developing their professionalism. This study employed a qualitative research method, utilizing data collection techniques such as observation, interviews, and document analysis. The respondents consisted of the school principal and 10 teachers Â from SMP Batik Surakarta. The research findings demonstrate that the school principal plays a central role as a learning leader in enhancing teacher professionalism. As a leader, the school principal provides clear directions and a strong vision to the teachers. They also offer relevant professional training and development, facilitate the exchange of ideas and best practices, and provide constructive feedback to assist teachers in improving their skills and knowledge. Furthermore, the school principal creates a collaborative and appreciative culture within the school, where teachers can support and work together to achieve common goals. The school principal also ensures the availability of adequate resources and a conducive learning environment for teachers to carry out their duties with professionalism. This research concludes that the role of the school principal as a learning leader is crucial in strengthening teacher professionalism at SMP Batik Surakarta. By taking this role seriously, the school principal can motivate and guide teachers to become more professional in their teaching, which, in turn, will have a positive impact on the quality of education in the school.Â